Acquired taste - Chapman, Clay McLeod (Titan Books, 2025)
"A father returns from serving in Vietnam with a strange and terrifying addiction; a man removes something horrifying from his fireplace, and becomes desperate to return it; and a right-wing news channel has its hooks in people in more ways than one. From department store Santas to ghost boyfriends and salamander-worshipping nuns; from the claustrophobia of the Covid-19 pandemic to small-town Chesapeake USA, Clay McLeod Chapman takes universal fears of parenthood, addiction and political divisions and makes them uniquely his own." --